2016
DOI: 10.1002/2016jd025119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Middle Eastern dust sources on PM10 in Iran: Highlighting the impact of Tigris‐Euphrates basin sources and Lake Urmia desiccation

Abstract: Contribution of different Middle Eastern dust origins to PM10 (PM with aerodynamic diameters less than 10 µm) levels in several receptor large cities in Iran was investigated. Initially, the major regional dust episodes were determined through statistical analysis of recorded PM levels at air quality stations and verified using satellite images. The particles dispersion was simulated by Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT) to regenerate PM10 during the dust episodes. The accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In particular, it is of primary importance to quantify the impact of climate factors, such as wind speed and precipitation, on the interannual variation of dust activities such that the contribution of anthropogenic activities during a specific period can be further identified. While the impact of upstream dust sources (Iraq, Syria, Saudi Arabia) on dust events over western Iran have been well investigated (e.g., Broomandi, Dabir, Bonakdarpour, & Rashidi, 2017b;Sotoudeheian, Salim, & Arhami, 2016), in this study, we focus on the impact of local meteorological factors (surface winds, precipitation, soil moisture) on dust phenomena over western and southwestern Iran.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is of primary importance to quantify the impact of climate factors, such as wind speed and precipitation, on the interannual variation of dust activities such that the contribution of anthropogenic activities during a specific period can be further identified. While the impact of upstream dust sources (Iraq, Syria, Saudi Arabia) on dust events over western Iran have been well investigated (e.g., Broomandi, Dabir, Bonakdarpour, & Rashidi, 2017b;Sotoudeheian, Salim, & Arhami, 2016), in this study, we focus on the impact of local meteorological factors (surface winds, precipitation, soil moisture) on dust phenomena over western and southwestern Iran.…”
Section: Introductionmentioning
confidence: 99%
“…A modeling study suggested that aerosol emitted from the lake bed can account for an estimated ~30–60% enhancement in PM 10 of nearby cities during dust episodes (Sotoudeheian et al, 2016), while other work suggests that crustal soil bordering LU, rather than lakebed salt, is the predominant source of aerosol emissions in the vicinity of LU (Gholampour et al, 2017). An examination of the spatiotemporal nature of aerosol around LU is highly relevant for the ~7.1 million people living in the lake’s watershed (http://irandataportal.syr.edu/census/census-2016., 2016) and ~80 million people living within a radius of 500 km (http://sedac.ciesin.columbia.edu/mapping/popest/gpw-v4/., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, larger AOD values begin in spring, reaching a maximum in summer, followed by a decrease in fall and winter. Furthermore, over Iraq, along the Mesopotamia plains, there is a distinct spatial northwestern pattern of aerosol loadings, in accordance with the prevailing shamal wind direction [12,13,[52][53][54]. Figure 6 shows that the seasonal variability in AOD indeed follows the general trend of increasing AOD toward spring-summer and a substantial decrease in fall-winter.…”
Section: Aod Change During Synoptically Calm Vs Stormy Periodsmentioning
confidence: 63%
“…Opposing viewpoints have been expressed in recently published papers, as well as in the mainstream media. One side argues that increased dust-storm activity is caused by human factors, such as the abandonment of agricultural land and reduced irrigation [11][12][13][14][15], while the other side counters with favorable meteorological conditions as the cause [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%